Imaginarios que tejen los niños en torno al tránsito escolar de preescolar a primero (2017)
This degree project has been carried out in order to identify what evokes in the child the transition of preschool to first grade school, to increase awareness of the importance of this event in the school life. This has been done by examining the narrative hermeneutic approach of the qualitative methodology, which proposes as a central axis the interpretation of realities narrated or observed, being thus a decisive factor, the constant contact with the population approached. Meanwhile, our research has ratified the value of referring to the significant influence on the child during this event, because they are the ones who experience feelings and emotions, as a consequence of the large number of changes that are faced. As a graduate in pre-school education at the University of San Buenaventura, we present the work as a proposal that focuses the research on this subject, so that the findings are real, meaningful and of greater practical application.